2010
DOI: 10.1007/s12010-010-9118-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biosurfactants on Laccase Production and Phenol Biodegradation in Solid-State Fermentation

Abstract: The effects of two biosurfactants, tea saponin (TS) and rhamnolipid (RL), on the production of laccase and the degradation of phenol by P. simplicissimum were investigated in solid-state fermentation consisting of rice straw, rice bran, and sawdust. Firstly, the effects of phenol on the fermentation process were studied in the absence of surfactants. Then, a phenol concentration of 3 mg/g in the fermentation was selected for detailed research with the addition of biosurfactants. The results showed that TS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Accordingly, we can assume the beneficial effect of the emulsifiers on diesel biodegradation through the increase of bacterial membrane permeability facilitating then substrates diffusion and/or metabolites and enzymes secretion. Many previous reports described the same findings for surfactants (Ji et al 2009;Gül and Dönmez 2012;Hadibarata et al 2013) or biosurfactants (Jadhav et al 2011;Zhou et al 2011). Moreover, as described in many other researches, surfactants could promote enzymes activities (Kristensen et al 2007;Champagne et al 2010;Zhang et al 2012).…”
Section: Estimation Of Diesel Biodegradation Potency and Gas Chromatosupporting
confidence: 70%
“…Accordingly, we can assume the beneficial effect of the emulsifiers on diesel biodegradation through the increase of bacterial membrane permeability facilitating then substrates diffusion and/or metabolites and enzymes secretion. Many previous reports described the same findings for surfactants (Ji et al 2009;Gül and Dönmez 2012;Hadibarata et al 2013) or biosurfactants (Jadhav et al 2011;Zhou et al 2011). Moreover, as described in many other researches, surfactants could promote enzymes activities (Kristensen et al 2007;Champagne et al 2010;Zhang et al 2012).…”
Section: Estimation Of Diesel Biodegradation Potency and Gas Chromatosupporting
confidence: 70%
“…Previous studies also showed that the addition of surfactants can increase the activity of laccase. For example, Zhou et al (2011) found that the addition of rhamnolipid and tea saponin can enhance the activity of laccase in solid-state fermentation. Ji et al (2009) found that the addition of Triton X-100 causes hydrophobic amino acid residues (Tyr, Trp, etc.)…”
Section: Various Dirl Concentrationsmentioning
confidence: 99%
“…Liu et al (2008) found that diRL has stimulative effects on the activities of carboxymethyl cellulose enzyme (CMCase), xylanase and lignin peroxidase from Phanerochaete chrysosporium in submerged fermentation. In our previous investigation, we also found that the presence of biosurfactant rhamnolipid can enhance the activity of laccase from Penicillium simplicissimum and the removal of phenol in solid-state fermentation (Zhou et al 2011). The objective of this study was to investigate the effect of the biosurfactant diRL on phenol removal catalyzed by laccase over the reaction in various water environments.…”
Section: Introductionmentioning
confidence: 96%
“…Curvularia lunata Phanerochaete chrysosporium [189] Polymeric model dye Poly R-478 Manganese peroxidase Irpex lacteus [141] Nonylphenol Laccase P. ostreatus [190] 2,4-dinitrophenol Laccase T. versicolor [191] Phenol Laccase P. simplicissimum [192] Naphthalene, Anthracene and Benzo[a]anthracene Laccase Lentinula edodes [193] Fluorene Laccase Coprinus plicatilis [194] Malachite green Laccase Bacillus thuringiensis [195] Bisphenol A Laccase Funalia trogii [196] Anthroquinone Laccase Lentinus sp [197] Salicylic acid, Naproxen, Ibuprofen, Gemfibrozil, Diclofenac and Triclosan Laccase Trametes versicolor [198] Bisphenol A and Diclofenac Laccase Aspergillus oryzae. [199] Endocrine Disrupters Laccase Cerrena unicolor [200] Textile effluent Laccase Pleurotus ostreatus IBL-02 and Coriolus versicolor [201] Dyes Peroxidase P.ostreatus [202] Olive [208] Methylene blue Mangenese peroxidase Phanerochaete chrysosporium [209] Versatile peroxidase and laccase Pleurotus ostreatus [210] coracryl brilliant blue, Ligninolytic enzymes Phanerochaete chrysosporium, Phlebia brevispora and Phlebia floridensis [211] graphene Lignin peroxidase White rot fungi [212] Sweet Sorghum Bagasse…”
Section: Compound Enzyme Organism Referencementioning
confidence: 99%